Crawford Howell Toy - Lyon, David G. (Harvard theological review, 1920)
“The earliest trace of the Toy family is found in England in the person of Robert Toy, bookseller in Saint Paul's Churchyard in 1640. Members of the family came to America about 1720, and settled first in New Jersey and then in Baltimore, whence Professor Toy's grandfather moved to Virginia about the beginning of this century” [19th]. This grandfather died in 1814 leaving an infant son, Thomas Dallam Toy, 1814–1879.